THE RELATIONSHIP OF PARENTS KNOWLEDGE AND SOCIOECONOMIC STATUS BASED ON PERFORMANCE TREATMENT INDEX - Namira Aulia Rizkia; Isnur Hatta; Fajar Kusuma Dwi Kurniawan (FKG Unlam, 2023)
ABSTRACTBackground: Dental and oral health problems are related to individual motivation to maintain oral and dental health. It is measured by the Performance Treatment Index (PTI). The average percentage of teeth decay, cavities and pain in Kotabaru regency is greater than the average percentage in South Kalimantan, which is 55.19% and the average percentage of filling in Kotabaru Regency is 2.72%. The level of knowledge and socioeconomic status affect individual motivation to maintain dental and oral health. Purpose: To analyze the relationship between knowledge of oral health and the socioeconomic status of parents with the Performance Treatment Index in students of SMPN 1 Kotabaru. Methods: This research is an analytic observational with a cross sectional approach. The sampling technique by simple random sampling with total 34 person. Results: The level of knowledge of parents on dental and oral health is mostly in the good category as many as 23 person (68%). The level of socioeconomic status of parents is mostly in the middle category with 21 person (62%). The level of Performance Treatment Index for SMPN 1 Kotabaru students is mostly in the category above the national standard with 15 person (44%). Spearman test results showed the relationship between parental knowledge and PTI with p value = 0.00 and a correlation coefficient of 0.719. The relationship between parents' socioeconomic status and PTI with p value = 0.00 and a correlation coefficient of 0.630. Conclusion: Based on on the research it can be concluded that there is a significant relationship between knowledge and socioeconomic status of parents with the Performance Treatment Index in students of SMPN 1 Kotabaru with a strong positive correlation. Keywords: Knowledge, Performance Treatment Index, Socioeconomic